Pendidikan Agama Islam Dalam Perspektif Antikorupsi: Membangun Generasi Yang Berintegritas - Fitri, Mutia; Zulfikar; Ramadhan, Muhammad; Martunisr (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
Corruption is a significant issue that hinders development in many countries, including Indonesia. Islamic religious education is believed to play a crucial role in shaping an anti-corruption character among the younger generation. This study aims to analyze how Islamic religious education can foster integrity and anti-corruption values by instilling moral values such as honesty (sidiq), trustworthiness (amanah), and justice (adil). The research method used in this study is library research, analyzing various recent literatures related to Islamic religious education and corruption prevention. The findings indicate that Islamic religious education has great potential in shaping an anti-corruption character by embedding these values. However, challenges faced in its implementation include the lack of understanding among educators regarding the importance of religion-based anti-corruption education and the influence of a social environment permissive towards corrupt practices. Therefore, collaboration between schools, families, and society is needed to create an environment that supports the application of Islamic values in everyday life, in order to form a generation that is both integral and free from corruption.